Comparative Study of Islamic Learning Practices in Early Childhood Institutions in Indonesia and Malaysia - Alfat Fahmi; Rizka Harfiani (Prodi Pendidikan Agama Islam, IAIN Sultan Amai Gorontalo, 2026)
Islamic Religious Education (IRE) at the early childhood level plays a crucial role in shaping children’s religious character from an early age. Although both Indonesia and Malaysia strongly emphasize Islamic education in preschool institutions, differences in curriculum policies and socio-cultural contexts are likely to produce distinct learning cultures. However, comparative studies specifically examining IRE learning culture at the early childhood level in both countries remain limited. Therefore, this study aims to comparatively analyze the learning culture of Islamic Religious Education at TK Aisyiyah Muhammadiyah in Indonesia and Tadika Alfikh Orchard in Malaysia. This research employed a descriptive qualitative comparative approach using observation, interviews, and document analysis, with data analyzed through the Miles, Huberman, and Saldana model. The findings indicate that Tadika Alfikh Orchard implements a modern and structured learning culture characterized by discipline, adab-oriented practices, and the integration of digital technology. In contrast, TK Aisyiyah Muhammadiyah demonstrates a more humanistic and flexible learning culture through religious habituation, teacher role modeling, and play-based learning. The study concludes that the differences in learning culture are shaped by national education policies and socio-cultural values. Malaysia emphasizes structure and standardization, while Indonesia prioritizes character formation through emotional closeness and religious habituation.